The Student's Disposition Mathematical Profile By Using Probability Theory Module - Nurmeidina, Rahmatya; Lazwardi, Ahmad; Ariyanti, Iin (Universitas Ahmad Dahlan, 2020)
The purpose of this study is to describe the profile of the Mathematical Disposition of mathematics education study programs on the use of probability theory modules. This research is a qualitative descriptive study. The subjects of this study were mathematics education students who were taking probability theory lectures. Data collection techniques are mathematical disposition questionnaires, interviews and documentation. Data analysis techniques using document analysis techniques. The results showed that the mathematical disposition of Mathematics Education study program students on the use of the Theory of probability module were in the high and very high categories. The mathematical disposition of students is reviewed from every aspect of the indicator in the high category. This study shows a description of the Mathematical Disposition profile of Mathematics Education study program students on the use of probability theory modules covering aspects of self-confidence, persistence, and perseverance, open or flexible thinking, interest, and curiosity, as well as monitoring and evaluating.